2000
DOI: 10.1074/jbc.m001151200
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Role of the Low Density Lipoprotein Receptor-related Protein against Amyloid β-Protein Toxicity

Abstract: In order to delineate the neuroprotective role of the low density lipoprotein receptor-related protein (LRP) against amyloid ␤-protein toxicity, studies were performed in C6 cells challenged with amyloid ␤-protein in the presence or absence of activated ␣ 2 -macroglobulin. Toxicity was assessed via two cell viability assays. We found that this endocytic receptor conferred protection against amyloid ␤-protein toxicity in the presence of activated ␣ 2 -macroglobulin and its down-regulation via inhibition by rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 47 publications
(39 reference statements)
1
24
1
Order By: Relevance
“…A putative role for LRP in AD is supported by in vitro studies showing that apoE and ␣ 2 M can form stable complexes with A␤ and promote its clearance via cell-surface LRP (5)(6)(7)(8)(9)(10). Furthermore, LRP appears to influence APP endocytic trafficking and cellular distribution such that processing to A␤ and its extracellular release are enhanced (11,12).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…A putative role for LRP in AD is supported by in vitro studies showing that apoE and ␣ 2 M can form stable complexes with A␤ and promote its clearance via cell-surface LRP (5)(6)(7)(8)(9)(10). Furthermore, LRP appears to influence APP endocytic trafficking and cellular distribution such that processing to A␤ and its extracellular release are enhanced (11,12).…”
mentioning
confidence: 72%
“…The low-density lipoprotein (LDL) receptor-related protein (LRP) has been genetically linked to AD (3,4) and has been shown to influence A␤ metabolism in vitro (5)(6)(7)(8)(9)(10)(11)(12). LRP is an Ϸ600-kDa cell-surface endocytic receptor member of the LDL receptor family (13).…”
mentioning
confidence: 99%
“…In addition, previous studies have shown that, in the presence of ␣2M, LRP protects neural cell lines against the neurotoxic effects of A␤ (Fabrizi et al, 1999;Van Uden et al, 1999b. These effects were blocked by exogenous administration of RAP and are dependent on calcium/calmodulin-dependent kinase 2 signaling (Van Uden et al, 2000). In hAPP tg mice, previous studies have shown that A␤ is synaptotoxic (Mucke et al, 2000b) and disrupts synaptic transmission independently of plaque formation (Hsia et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…After the addition of 0.4% trypan blue for 2 min (Sigma), the percent of dead cells (trypan bluestained) was recorded within 10 min and visualized with an Axiovert inverted microscope. In addition, a DNA fragmentation assay was performed as previously described (38). Briefly, cells (1 ϫ 10 6 ) were washed and collected by centrifugation.…”
Section: Methodsmentioning
confidence: 99%